The Teen Screen for Dating Violence: An Item Response Theory Analysis. Issue 17 (September 2021) - Emelianchik-Key, Kelly; Colvin, Kimberly F.
There continues to be a lack of fundamental knowledge regarding assessment, conceptualization, and treatment of teen dating violence (TDV). This deficiency of knowledge becomes even greater when examining gender differences in violence experience, perpetration, and perception. This article details the item response theory (IRT) analysis of the Teen Screen for Dating Violence (TSDV) and includes an assessment of differential item functioning (DIF) reported by gender. The TSDV examines adolescents' perception, experience, perpetration, and exposure to violence, while also exploring support systems. The study participants included males and females between 13 and 21 years of age. Further refinement of the TSDV contributes to a more accurate and comprehensive conceptualization of TDV measurement. The results of this study support the use of the TSDV to assess for TDV in the adolescent population. The DIF analysis reveals that many of the items function differently for males and females, which provides evidence indicating that how TDV is experienced, perceived, and perpetrated differs across gender. The TSDV can assist clinicians in early TDV prevention, intervention, and education for males and females. It can also assist researchers in more accurately estimating perpetration, experience, and conceptualization of the three violence facets (emotional, physical, and sexual) in males and females. To further expand TDV knowledge, we offer recommendations for the use of the TSDV in various settings. The TSDV is a vital tool for clinicians, supervisors, and researchers to implement to mitigate the TDV epidemic and help bridge the gap in mental health services.